Analisis Rantai Pasok Komoditi Jagung Di Desa Tumani Selatan Kecamatan Maesaan Kabupaten Minahasa Selatan - Lantu, Melisa Santi; Sondakh, Mex Frans Lodwyk; Kaunang, Rine (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the corn supply chain in South Tumani Village, Maesaan District, South Minahasa Regency. Data collection in this study uses two types of data, namely primary data and secondary data. Respondents in this study were those involved in the corn supply chain, namely farmers, collectors, and consumers in Kawangkoan and Sonder. The results showed that the corn supply chain in Tumani Selatan Village consisted of Farmers-Traders-Collectors-Consumers in Kawangkoan and Sonder. The product flow starts from the farmers harvesting the corn and then selling the corn to the collectors and then the collecting traders distribute the corn to consumers in Kawangkoan and Sonder. The financial flow starts from consumers buying corn from collectors at a price of IDR 5,300/Kg with a transfer transaction system via bank then the collector buys corn from farmers at a price of IDR 4,800/Kg with a direct system (cash). The flow of information flows from two directions, the first direction is that consumers from Kawangkoan and Sonder inform the collecting traders that they need 3,000 kg for consumers at Kawangkoan and 3,000 kg for consumers at Sonder, then the collecting traders inform the corn price to farmers, namely IDR 4,800/Kg. The second direction is that the farmers inform the collectors about the availability of corn and provide information on the location where the corn is taken, then the collectors inform the consumers about the corn to be sold.